Hormonal and spatial control of SUMOylation in the human and mouse adrenal cortex. Issue 9 (17th June 2019) - Dumontet, Typhanie; Sahut‐Barnola, Isabelle; Dufour, Damien; Lefrançois‐Martinez, Anne‐Marie; Berthon, Annabel; Montanier, Nathanaëlle; Ragazzon, Bruno; Djari, Cyril; Pointud, Jean‐Christophe; Roucher‐Boulez, Florence; Batisse‐Lignier, Marie; Tauveron, Igor; et al.
ABSTRACT: SUMOylation is a highly conserved and dynamic post‐translational mechanism primarily affecting nuclear programs for adapting organisms to stressful challenges. Alteration of SUMOylation cycles leads to severe developmental and homeostatic defects and malignancy, but signals coordinating SUMOylation are still unidentified. The adrenal cortex is a zonated endocrine gland that controls body homeostasis and stress response. Here, we show that in human and in mouse adrenals, SUMOylation follows a decreasing centripetal gradient that mirrors cortical differentiation flow and delimits highly and weakly SUMOylated steroidogenic compartments, overlapping glomerulosa, and fasciculata zones. Activation of PKA signaling by acute hormonal treatment, mouse genetic engineering, or in Carney complex results in repression of small ubiquitin‐like modifier (SUMO) conjugation in the inner cortex by coordinating expression of SUMO pathway inducers and repressors. Conversely, genetic activation of canonical wingless‐related integration site signaling maintains high SUMOylation potential in the outer neoplastic cortex. Thus, SUMOylation is tightly regulated by signaling pathways that orchestrate adrenal zonation and diseases.—Dumontet, T., Sahut‐Barnola, I., Dufour, D., Lefrançois‐Martinez, A.‐M., Berthon, A., Montanier, N., Ragazzon, B., Djari, C., Pointud, J.‐C., Roucher‐Boulez, F., Batisse‐Lignier, M., Tauveron, I., Bertherat, J., Val, P., Martinez, A. Hormonal and spatial control of SUMOylation in the human and mouse adrenal cortex. FASEB J. 33, 10218–10230 (2019). www.fasebj.org